Consumer Motivation for Reward Pursuit: A Culture-Based and Progress-Based Model of Loyalty Program Effectiveness. Issue 4 (8th August 2019) - Yang, Morgan X.; Chan, Haksin; Yu, Irina Y.; Fock, Henry
Abstract: Aided by the exponential rate of globalization and digitalization, reward or loyalty programs (LPs) have attained global reach. Paradoxically, however, dropout rates of LPs have averaged over 75%. This disconcerting statistic, coupled with the lack of culture-specific insights in the literature, points to a research area of great theoretical and practical importance. To address the aforementioned issues, we develop a culture-based and progress-based model of consumer motivation that is especially applicable to LP members. Drawing on cross-cultural literature and goal pursuit theory, our research enriches a field that is inherently global in nature. Through a series of research propositions that elucidate how Western individualist (vs. Eastern collectivist) consumers are differentially motivated to pursue LP rewards, we advance theoretical understanding of reward-induced behavior across cultures and offer useful insights for global managers of LPs.